Consecutive Nucleation and Confinement Modulation towards Li Plating in Seeded Capsules for Durable Li‐Metal Batteries. Issue 25 (11th May 2021) - Huang, Minsong; Yao, Zhenguo; Yang, Qifan; Li, Chilin
Abstract: A dual modulation strategy of consecutive nucleation and confined growth of Li metal is proposed by using the metal–organic framework (MOF) derivative hollow capsule with inbuilt lithiophilic Au or Co‐O nanoparticle (NP) seeds as heterogeneous host. The seeding‐induced nucleation enables the negligible overpotential and promotes the inward injection of Li mass into the abundant cavities in host, followed by the conformal plating of Li on the outer surface of host during discharging. This modulation alleviates the dendrite growth and volume expansion of Li plating. The interconnected porous host network enables enhancement of cycling and rate performances of Li metal (a lifespan over 1200 h for Au‐seeding symmetric cells, and an endurance of 220 cycles under an ultrahigh current density of 10 mA cm −2 for corresponding asymmetric cells). The hollow capsules integrated with lithiophilic seeds solve the deformation problem of Li metal for durable and long‐life Li‐metal batteries. Abstract : A dual modulation strategy of consecutive nucleation and confined growth of Li metal is proposed by using the metal–organic framework (MOF) derivative hollow capsule with inbuilt lithiophilic Au or Co‐O nanoparticle (NP) seeds as heterogeneous host.